PENGARUH LINGKUNGAN KERJA, KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Hutami, Meidina Putri; Suwarto, FX. (JURNAL LENTERA BISNIS, 2026)
Performance monitoring in hospitals is crucial, as they provide essential public health services. Hospitals must thoroughly evaluate clinical pathway quality to ensure an effective and efficient system. This study aims to analyze the effects of work environment, transformational leadership, and motivation on employee performance, with job satisfaction as a mediating variable, among nurses and midwives in private hospitals in the Jabodetabek area. A quantitative approach was used, with questionnaires distributed to 210 respondents. Data were analyzed using path analysis with Smart PLS 4.0 software and the Structural Equation Model (SEM) method to examine direct and indirect relationships among variables. The results showed that work environment, transformational leadership, and motivation have a positive and significant effect on employee performance. These findings highlight that job satisfaction plays a key role in strengthening the relationship between work environment, transformational leadership, and motivation with performance. The managerial implications emphasize the importance of creating a supportive work environment, developing transformational leadership, and enhancing employee motivation to improve job satisfaction and performance. This study also contributes theoretically by providing empirical evidence on the mediating role of job satisfaction in the healthcare sector, especially in private hospitals.